Sosialisasi Bela Negara Desa Gammawar Lawe Sagu Hulu kecamatan Lawe Bulan Di Kabupaten Aceh Tenggara - Bahrul Ilmi (CV. Armas Suan Sejahtera, 2025)
This community service initiative focuses on enhancing national defense awareness in Gammawar Village, Southeast Aceh, a border area. The program was motivated by the community's limited understanding of contemporary national defense concepts, which were previously confined to military aspects. The objectives include developing a comprehensive understanding of national defense, building awareness of non-military threats, and establishing village-level defense cadres. Implementation methods involved a three-day participatory workshop combining interactive socialization, focused group discussions, conflict resolution simulations, and action plan mentoring. Evaluation results demonstrated significant improvement in participants' understanding, from 45% to 82% based on pre- and post-test results. Short-term benefits include a shift in community perception towards viewing national defense as a collective responsibility. Long-term sustainability is ensured through the formation of 15 village defense cadres and the preparation of a 2024-2026 National Defense Action Plan. This initiative not only strengthens community resilience but also serves as a replicable model for other villages with similar characteristics.